Intra-Abdominal Hypertension and Gastrointestinal Symptoms in Mechanically Ventilated Patients - Annika Reintam Blaser; Pille Parm; Reet Kitus; Joel Starkopf (Critical Care Research and Practice)
Background. We aimed to describe the incidence of intra-abdominal hypertension (IAH) and gastrointestinal (GI) symptoms and related outcome in mechanically ventilated (MV) patients. Methods. Intra-abdominal pressure (IAP) and gastric residual volumes were measured at least twice daily. IAH was defined as a mean daily value of IAP≥12 mmHg. Results. 398 patients were monitored for all together 2987 days. GI symptom(s) occurred in 80.2% patients. 152 (38.2%) patients developed IAH. Majority (93.4%) of patients with IAH had GI symptoms. The more severe IAH was associated with the higher number of concomitant GI symptoms (P<.001). 142 (35.7%) patients developed both IAH and at least one GI symptom at any time in ICU, and in 77 patients they occurred simultaneously on the same day. This subgroup had the highest ICU mortality (21.8%). In contrast, the small group of patients presenting only IAH, but not GI symptoms (10 patients), had no lethal outcome. Three patients (4.4%) died without showing either IAH or GI symptoms. Conclusions. GI symptoms and IAH often, but not always, occur together. The patients having IAH solely without developing GI symptoms have rather good outcome.